2007
DOI: 10.1111/j.1939-1676.2007.tb02960.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Stage, Therapy, and Prognosis in Canine Anal Sac Gland Carcinoma

Abstract: Background: Reports of canine anal sac gland carcinoma (ASGC) describe varied clinical presentations and management and differing responses to therapy. A unifying approach to clinical stage determination and management of this disease has yet to be presented.Hypothesis: An ordinal clinical staging scheme for canine ASGC can be devised on the basis of responses to therapy for a retrospective cohort of affected dogs.Animals: 130 dogs with naturally occurring ASGC. Methods: A simplified clinical stage system and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
168
3
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(194 citation statements)
references
References 10 publications
16
168
3
7
Order By: Relevance
“…Age (mean, 10.4 years), body weight (mean, 27 kg), and breeds in the present study were consistent with those in earlier studies. 1,5,7,9,10 Similar to Williams et al, 7 the present study found an ASAC in a dog as young as 7.2 years of age.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Age (mean, 10.4 years), body weight (mean, 27 kg), and breeds in the present study were consistent with those in earlier studies. 1,5,7,9,10 Similar to Williams et al, 7 the present study found an ASAC in a dog as young as 7.2 years of age.…”
Section: Discussionsupporting
confidence: 87%
“…1,5,7,10 In contrast, in studies 8,9,17,18 published prior to 1992, 79% to 100% of dogs were female. All 42 dogs in the present study were spayed or neutered, suggesting that ASACs may not require hormonal influences to develop.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The demographics of our study population were consistent with previous reports, providing support for an accurate representation of dogs with AGASACA. [1][2][3][4][5]30 Most dogs treated in the macroscopic disease setting (69%) experienced clinical benefit from treatment (20.7%, PR; 48.3%, SD) and clinical benefit was positively associated with OST and PFS. These response outcomes are consistent with previous reports.…”
Section: Discussionsupporting
confidence: 75%